Mental Health and Placenta Accreta Spectrum - Salama, Kate; Holt, Roxane; Puryear, Lucy J. (American Journal of Perinatology, 2023)
Nearly half of women describe childbirth as traumatic in some way, making them more vulnerable to perinatal psychiatric illness. Patients with high risk pregnancies, such as abnormal placentation, are even more susceptible to childbirth related mental health sequelae. There are no formal recommendations for mental health intervention in women with placenta accreta spectrum (PAS). In many institutions, the Edinburgh Postpartum Depression Scale is used to assess for depressive and anxiety symptoms during pregnancy and postpartum. Women with PAS should be screened at time of diagnosis, monthly until delivery, and at multiple time points through the first year postpartum. It is also recommended to screen women for PTSD prior to and after delivery. Interventions shown helpful in the PAS population include establishing a multidisciplinary team, patient access to a support person or care coordinator, development of a postpartum care team and plan, and extending mental health follow up through the first year postpartum. Women with PAS are at increased risk for negative mental health outcomes. To support the mental health of women with PAS and their families, we recommend a multi-disciplinary treatment team, screening for mental health sequelae early and often, referring women with positive screens to mental health professionals, involving the partner/family in care, and considering referral to a PAS support group for peer support.
Keywords: placenta accreta; pregnancy; mental health; postpartum depression; posttraumatic stress disorder